O papel dos custos de transação na prestação dos serviços urbanos de infraestrutura: um panorama dos municípios brasileiros e portugueses - Lucca, Paulo Vitor (2021)
The theme of this study is the delivery of urban infrastructure services in large Portuguese and Brazilian municipalities. With the reduction of resources and the increase in demand, large cities need efficient instruments to provide urban services to improve the level of service provided to the population. This improvement in services ends up reflecting on the quality of life and economic development, in addition to being directly related to the capacity of institutions to find the most adequate governance structures. In this context, the use of Transaction Cost Theory (TCT), in its economic and political aspects, seems to be an appropriate lens for research that seeks to understand the ways in which public services are provided. Several empirical studies around the world have been developed to understand how governance structures (hierarchy, market and networks) can be explained based on TCT. However, for the Brazilian reality, studies in this sense were not found in a synthetic and organized way. On the other hand, Portugal has developed studies in this area, however, with the dynamic process in which the provision of public services takes place, it becomes interesting to update such studies in order to expand the existing database. The aim of this study was to build an overview of the options for providing ten urban infrastructure services in large municipalities in Brazil and Portugal, and verify if the TCT parameters can be applied to justify the organization of these services in both countries. It was considered a quantitative approach and statistical treatment, in which data were obtained through questionnaires sent to selected municipalities and collection of information on the official portals of the municipalities and other official bodies. The results showed that, while in Brazil the option is mostly for market structures, in Portugal the preference is for hierarchies, as found in other studies. The TCT, from an economic point of view, presented inconclusive statistical results, however, it was found that the existence of evaluation of services, as a measurement parameter, leads to externalization in the case of Brazil. In relation to political transaction costs, it was found that the economy of scale, poor financial health, direct charging for services and the high population density are consistent with the trend of externalization in the Brazilian, but not in the Portuguese context. Electoral cycles are not able to change the ways in which urban infrastructure services are provided, possibly because these services are technical in nature. Administrative stability was not identified as a factor influencing decision-making on governance structures.